2017
DOI: 10.21032/jhis.2017.42.1.10
|View full text |Cite
|
Sign up to set email alerts
|

Secular Trend of Gestational Age Specific Preterm Birth Rate in Korean Singleton and Multiple Birth: 1997-98, 2013-14

Abstract: Background: International comparison and time trend surveillance of preterm delivery rates is complex. New techniques that could facilitate interpretation of such rates are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This possibility is supported by the larger proportion of late preterm births among the prematurity population and the lower proportion of twins with birth weight discordance. In addition, in the case of twins, unlike that of singletons, the delivery time is determined according to chorionicity and amnionicity [ 12 , 13 ]. The American College of Obstetricians and Gynecologists suggested that obstetricians consider delivering twins in the preterm to early term according to their chorionicity.…”
Section: Discussionmentioning
confidence: 99%
“…This possibility is supported by the larger proportion of late preterm births among the prematurity population and the lower proportion of twins with birth weight discordance. In addition, in the case of twins, unlike that of singletons, the delivery time is determined according to chorionicity and amnionicity [ 12 , 13 ]. The American College of Obstetricians and Gynecologists suggested that obstetricians consider delivering twins in the preterm to early term according to their chorionicity.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical pessary use or cervical cerclage prevents repeated preterm births in high-risk women with a short cervix 18 . Despite medical advances, the rate of preterm births increased from 2.9% (1997–1999) to 4.5% (2011–2013) 19 and from 3.31% (1997–1998) to 6.44% (2013–2014) 20 in Korea. The increase in twin births is thought to have contributed to the rise in preterm births.…”
Section: Discussionmentioning
confidence: 99%
“…[18] Despite medical advances, the rate of preterm births increased from 2.9% (1997-1999) to 4.5% (2011-2013) [19] and from 3.31% (1997-1998) to 6.44% (2013-2014) [20] in Korea. The increase in twin births is thought to have contributed to the rise in preterm births.…”
Section: ) Preterm Birthmentioning
confidence: 99%